Comparative effectiveness of treatments on time to remission in atopic dermatitis: real-world insights - Emi Sato; Hisatomi Arima; Kotaro Ito; Mayuko Iwata; Shinichi Imafuku (Frontiers Media S.A., 2024)
IntroductionIt remains unclear which therapy contributes to atopic dermatitis (AD) remission and to what extent. We aimed to clarify which therapy contributes to the treatment of AD by investigating the time-to-remission and remission hazard ratios for each therapy using real-world data.MethodsThis retrospective cohort study included 110 patients diagnosed with AD after their first visit to the Department of Dermatology at Fukuoka University Hospital between 2016 and 2022. The patients were categorized into six treatment groups: 1) topical treatment alone or topical treatment plus 2) ultraviolet light, 3) oral steroids, 4) oral cyclosporine, 5) dupilumab, and 6) oral Janus kinase inhibitors (JAKi). The topical therapy alone group served as the control, and the hazard ratios for remission (Investigator's Global Assessment [IGA] 0/1) were calculated.ResultsForty patients achieved remission, while 70 did not (IGA ≥2) with the first treatment regimen. A multivariate Cox proportional hazards analysis adjusted for age, sex, and severity at the first visit (IGA) revealed that the hazard ratios for remission were 4.2 (95% confidence interval (C.I.): 1.28-13.83, p = 0.018) for the oral cyclosporine group, 5.05 (95% C.I.: 1.96-13, p = 0.001) for the dupilumab group, and 67.56 (95% C.I.: 12.28-371.68, p < .0001) for the oral JAKi group. The median time to remission was 3 months for JAKi, cyclosporine, and steroid was shorter than 6 months for dupilumab. No serious adverse events were observed.ConclusionOral therapy with small molecules requires a shorter duration to achieve remission. However, long-term safety and recurrence are important indicators.